2019
DOI: 10.1096/fj.201900257r
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation, cognitive impairment, and distal brain region alteration following intracerebral hemorrhage

Abstract: Delayed cognitive decline commonly occurs following intracerebral hemorrhage (ICH), but the mechanisms underlying this phenomenon remain obscure. We therefore investigated the potential mechanisms responsible for impaired cognitive function in a mouse collagenase model of ICH. Following recovery of motor and sensory deficits in the chronic phase of ICH, we noted significant cognitive impairment, which was assessed by the Morris water maze. This finding was accompanied by reduced dendrite spine density of ipsil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 39 publications
5
18
1
Order By: Relevance
“…In agreement with our ndings, Cope and colleagues recently found that microglial activation plays an active role in obesity-associated cognitive decline since blocking microglial activation by minocycline prevented loss of dendritic spine and cognitive decline in obese mice [45]. Depletion of microglia by CSF1R inhibitors, such as PLX3397 and PLX5622, was also associated improved cognitive performance in experimental mouse models of AD [46], intracerebral hemorrhage [47] and irradiation-induced memory de cits [48].…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with our ndings, Cope and colleagues recently found that microglial activation plays an active role in obesity-associated cognitive decline since blocking microglial activation by minocycline prevented loss of dendritic spine and cognitive decline in obese mice [45]. Depletion of microglia by CSF1R inhibitors, such as PLX3397 and PLX5622, was also associated improved cognitive performance in experimental mouse models of AD [46], intracerebral hemorrhage [47] and irradiation-induced memory de cits [48].…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with brain injury in cardiac arrest rats being attenuated by blocking HMGB1 activity [91]. These associations of biomarkers and mediators in AD and PD are consistent with the therapeutic implications of recent detailed analyses of global inflammation in experimental stroke [94], intracerebral hemorrhage [95], and TBI [96]…”
Section: Changes In Triggering Receptor Expressed Onsupporting
confidence: 77%
“…Other studies [31,32] confirmed that cortical infarction can lead to hippocampal atrophy, metabolic dysfunction, and memory decline. Recently, Shi et al detected significant cognitive impairment after basal ganglia hemorrhage, accompanied by reduced spine density on ipsilateral hippocampus neurons [33]. In the present study, we found that cognitive function is diminished as early as week 1 after ICH, and whole brain-based analysis of DTI data showed a decline in FA values in the ipsilateral hippocampus.…”
Section: Agingsupporting
confidence: 70%